IMPLEMENTATION OF C4.5 ALGORITHM TO ASSIST IN THE SELECTION OF FLOOR CONSTRUCTION PROJECTS - Aditya Roval Lendra; Diky Firdaus (IJISCS (International Journal of Information System and Computer Science), 2020)
The country of Indonesia is a developing country. This is indicated by the improvement of the development process and business. So, many development projects will appear. With the changing world in the industry with e-Government governance, project data is no longer in paper form. With the emergence of data - a lot of companies need to do project management activities in determining the project strategy to be taken so as not to affect the final results in determining the taking of the project. Then do a lot of research on the project data that appears in the construction world. The method used for this research is the C4.5 Algorithm which is one of the modern algorithms for data mining processes. C4.5 algorithm is also called a decision tree (decision tree) which is one of the classification methods with a tree structure representation. The concept is to collect data and be made into a decision tree based on the rules needed to get an outcome. The pattern and results obtained will be used for recommendations in determining which projects the company will take. The values generated using Rapidminer are Accuracy 97.18%, precision 100%, and recall 94.31%. With the result, 1205 recommended floor construction projects were taken and 784 projects were recommended not to be taken.